Paradigma Baru Konsumsi Islami: Islamisasi Konsep Utilitas Sebagai Kritik Atas Ekonomi Konvensional - Wibisono, Vina Fithriana; Arief, Suyoto; Atmaja, Mukti Tri (Lembaga Penelitian dan Pengembangan Masyarakat IAINU Kebumen, 2025)
Consumption is a routine activity that is often influenced by a culture of satisfaction-based consumerism. Islamization of science is needed to direct consumption behavior towards benefit according to Islamic value. Islamization of science is crucial, as Western perspectives often incorporate values that conflict with Islamic viewed. This research aims to redefining the utility concept of consumption behavior by presenting Islamization, as solution to the deficiencies in the basis of conventional economics science. The method in this research is library research with conceptual approach and descriptive analysis using literature review from source which are related to this topic. The result of this research show that Western consumption behavior emphasizes that satisfaction (utility) increases with higher use value or maximum utilization (ishraf or excessive and raghbah or desires), while Islamic consumption bases use value on maslahah; level of utility based on usefulness and blessing (barakah); and base scale in prioritizing need by applying maqashid sharia.